Machine vision beyond visible spectrum - Hammoud, Riad.; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
The material of this book encompasses many disciplines, including visible, infrared, far infrared, millimeter wave, microwave, radar, synthetic aperture radar, and electro-optical sensors as well as the very dynamic topics of image processing, computer vision and pattern recognition. This book is composed of six parts: Advanced background modeling for surveillance Advances in Tracking in Infrared imagery Methods for Pose estimation in Ultrasound and LWIR imagery Recognition in multi-spectral and synthetic aperture radar Fusion of disparate sensors Smart Sensors.
1. Target Recognition in Infrared: Local Feature Based Person Detection and Tracking Beyond the Visible Spectrum -- Fuzzy mixture of Gaussians for the detection of moving objects in and beyond visible spectrum -- Dynamic Appearance Learning by Adaptive Kalman Filters for Robust Infrared Tracking -- Pedestrian Association and Localization in Monocular FIR Video Sequence -- Vehicle Matching and Recognition under Large Variations of Pose and Illumination -- 2. Multi-Sensor Fusion and Smart Sensors: Fusion of a Camera and a Laser Range Sensor for Vehicle Recognition -- Geometric Sequence (GS) Imaging with Bayesian Smoothing for Optical and Capacitive Imaging Sensors -- A System Approach to Adaptive Multimodal Sensor Designs.-3. Hyperspectral Image Analysis: Statistical Affine Invariant Hyperspectral Texture Descriptors Based Upon Harmonic Analysis -- Face Tracking and Classification Using Hyperspectral Video Sequences -- On near real-time moving Object Detection and Tracking in Multi-spectral Aerial imagery.
Electronic reproduction.
Keywords: Electronic books; Computer vision